2019
DOI: 10.1039/c8ra07645f
|View full text |Cite
|
Sign up to set email alerts
|

In situ phytoremediation of copper and cadmium in a co-contaminated soil and its biological and physical effects

Abstract: Phytoremediation is a potential cost-effective technology for remediating heavy metal-contaminated soils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…were lower than the Cd hyperaccumulator (Sedum plumbizincicola), and Cu concentrations lower than in the Cu tolerant Elsholtzia splendens, Pennisetum sp. accumulated and removed more Cd and Cu due to its much larger biomass (Xu et al 2019). However, soil Cd concentration was very low (<0.42 mg/kg) and 1% hydroxyapatite was added in that study.…”
Section: Discussionmentioning
confidence: 70%
“…were lower than the Cd hyperaccumulator (Sedum plumbizincicola), and Cu concentrations lower than in the Cu tolerant Elsholtzia splendens, Pennisetum sp. accumulated and removed more Cd and Cu due to its much larger biomass (Xu et al 2019). However, soil Cd concentration was very low (<0.42 mg/kg) and 1% hydroxyapatite was added in that study.…”
Section: Discussionmentioning
confidence: 70%
“…For example, Pennisetum sp. has higher biomass compared to both the Cd hyperaccumulator Sedum Plumizincicola and the Cu tolerant Elsholtzia splendens , so it can accumulate and remove more Cd and Cu (Xu et al 2019 ). From these perspectives, ornamental shrubs may be a better substitute for herbs.…”
Section: Discussionmentioning
confidence: 99%
“…was found to be the best species for Cu and Cd removal. 12 Also, the biomasses of Elsholtzia splendens and Sedum plumbizincicola were found to be good species for Cu and Cd removal. 12 The obtained results showed that the functionalized halloysite nanotubes enhanced the adsorption capability of the clay mineral and it made nanoclay a good candidate for heavy metal removal from aqueous solutions.…”
Section: Introductionmentioning
confidence: 91%
“…12 Also, the biomasses of Elsholtzia splendens and Sedum plumbizincicola were found to be good species for Cu and Cd removal. 12 The obtained results showed that the functionalized halloysite nanotubes enhanced the adsorption capability of the clay mineral and it made nanoclay a good candidate for heavy metal removal from aqueous solutions. 13 Physicochemical procedures comprise adsorption, ion exchange, membrane ltration, and chemical precipitation.…”
Section: Introductionmentioning
confidence: 91%